Social Media and Online Application Effectiveness in Increasing Domestic and International Tourists Interest in Visiting Indonesia’s Marine Tourism - Putri, Vathya Anindita; Tairas, David Ronald (Global Writing Academica Researching & Publishing, 2024)
This research examines the use of Social Media as ICTs and Online Applications in the interest of domestic and foreign tourist to visit marine tourism in Indonesia, the 2019 pandemic had a major impact on the tourism sector, especially marine tourism. The Ministry of Tourism and Creative Economy shows that the decline in foreign tourists has had a direct impact on the occupancy of hotels in Indonesia. In 2020 January-February, occupancy is still at 49.17% and 49.22%. In March it became 32.24%, and worsened in April, which was 12.67%. Post-pandemic, BPS data has seen a significant increase in the number of visitors visiting tourist attractions in Indonesia, the use of social media and online applications has encouraged foreign and domestic tourists. In this study, the Mixmethod research method was used to examine the use of social media and Online application effectiveness for tourists' interest in visiting marine tourism in Indonesia.